Activation of Rev-erbα attenuates lipopolysaccharide-induced inflammatory reactions in human endometrial stroma cells via suppressing TLR4-regulated NF-κB activation. (14th August 2019) - Zhao, Weijie; Cui, Liyuan; Huang, Xixi; Wang, Songcun; Li, Dajin; Li, Liping; Sun, Yan; Du, Meirong
Abstract: Perturbation of the circadian rhythm damages the biological characteristics of cells and leads to their dysfunction. Rev-erbα, an important gene in the transcription-translation loop of circadian rhythm, is involved in regulating the balance between pro-inflammation and anti-inflammation. The disruption of this balance in human endometrial stroma cells (hESCs) destroys their biological behavior function in maintaining the menstrual cycle and embryonic implantation. Whether pharmacological modulation of Rev-erbα affects the inflammation of hESCs remains unclear. In this study, we treated hESCs with lipopolysaccharide (LPS) and found that LPS treatment increased the mRNA levels of pro-inflammatory cytokines, such as interleukin (IL)-1β, IL-6, IL-8, IL-18, and TNFα, and the secretion of IL-6. SR9009, a Rev-erbα agonist, significantly alleviated the LPS-induced production of pro-inflammatory cytokines in hESCs. Meanwhile, knockdown of Rev-erbα increased the expressions of IL-1β, IL-6, and IL-8, accompanied by an increased mRNA level of the core clock gene Bmal1 . Western blot analysis showed that SR9009 inhibited the expression of toll-like receptor 4 (TLR4) and the activation of NF-κB induced by LPS. All these findings suggested that pharmacological activation of Rev-erbα attenuated the LPS-induced inflammatory response of hESCs by suppressing TLR4-regulated NF-κB activation. This study may provide a strategy for preventing inflammation-related endometrial dysfunction and infertility or recurrent implantation failure.